MENUMBUHKAN BUDAYA LITERASI MEMBACA DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PADA ANAK USIA SEKOLAH DASAR - Adelina Br. Sembiring; Ainun Mardiah; Manna Wassalwa; Nabila Suhaila Lubis; Try Suci Prastiwi (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
Low literacy skills lead to low interest in reading among students, especially elementary school children. One of the government's steps in an effort to increase students' interest in reading is the School Literacy Movement (GLS) program. The effort made is by reading for 15 minutes, the books read start from story books and comic books according to what elementary school children like. The purpose of this research is to foster students' interest in reading which has been lost due to the influence of globalization in this modern era. Where elementary school children nowadays play gadgets more often than reading books, especially their school books. This study used a qualitative approach with the library research method. The object of study and data analysis is carried out by reviewing several relevant journals and various reports related to the problem to be solved. The results of the study show that the literacy movement can foster interest in reading in elementary school students. Because in general children like to read stories, such as comic stories or fables that have interesting pictures.